Characterization and phylogenetic analysis of the complete mitochondrial genome of invasive Pontastacus leptodactylus in China - Huiyi Cai; Honglin Chen; Huan Zhou; Xiaojun Xu; Wenzhi Guan; Xuping Shentu; Bao Lou (Aquaculture Reports, 2025)
The spread of invasive crayfish species poses a serious threat to the freshwater ecosystems. However, it is also a chance to enrich the resources for crayfish genetic resource. A species of crayfish from family Astacidae was discovered in Xinjiang of China in 2019, in order to accurately determine its taxonomic affiliation and origin, the mitochondrial genome was sequenced and the phylogenetic trees were constructed with other species in the study. The mitogenome of the crayfish consisted of 15,449 base pairs including 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, and 2 ribosome RNA (rRNA) genes, with a base composition of the A (33.63 %), G (16.42 %), C (10.86 %), and T (39.1 %). The start codons of all PCGs were in the ATN form (ATG, ATA and ATT) except for atp8 (GTG). The phylogenetic tree showed that the crayfish found in Xinjiang of China clustered with Pontastacus leptodactylus. The phylogenetic trees based on cox1 and 16S rRNA revealed that the crayfish was more closely related to the P. leptodactylus from Asia, while haplotype analyses revealed shared haplotypes between Xinjiang (China) and Asian individuals for both genetic markers. These results demonstrate a close evolutionary relationship between the crayfish from Xinjiang of China and the Asian lineage. Our study both resolves the immediate taxonomic identification and provides important reference data for the study of mitochondrial genome evolution and mitochondrial function in the future.